Free radical production and antioxidant status in brain cortex non-synaptic mitochondria and synaptosomes at alcohol hangover onset - Karadayian, Analia Graciela (2017)
Alcohol hangover (AH) is the pathophysiological state after a binge-like drinking. We have previously demonstrated that AH induced bioenergetics impairments in a total fresh mitochondrial fraction in brain cortex and cerebellum. The aim of this work was to determine free radical production and antioxidant systems in non-synaptic mitochondria and synaptosomes in control and hangover animals. Superoxide production was not modified in non-synaptic mitochondria while a 17.5% increase was observed in synaptosomes. A similar response was observed for cardiolipin content as no changes were evidenced in non-synaptic mitochondria while a 55% decrease in cardiolipin content was found in synaptosomes. Hydrogen peroxide production was 3-fold increased in non-synaptic mitochondria and 4-fold increased in synaptosomes. In the presence of deprenyl, synaptosomal H2O2 production was 67% decreased in the AH condition. Hydrogen peroxide generation was not affected by deprenyl addition in non-synaptic mitochondria from AH mice. MAO activity was 57% increased in non-synaptic mitochondria and 3-fold increased in synaptosomes. Catalase activity was 40% and 50% decreased in non-synaptic mitochondria and synaptosomes, respectively. Superoxide dismutase was 60% decreased in non-synaptic mitochondria and 80% increased in synaptosomal fractions. On the other hand, GSH (glutathione) content was 43% and 17% decreased in synaptosomes and cytosol. GSH-related enzymes were mostly affected in synaptosomes fractions by AH condition. Acetylcholinesterase activity in synaptosomes was 11% increased due to AH. The present work reveals that AH provokes an imbalance in the cellular redox homeostasis mainly affecting mitochondria present in synaptic terminals.